Performance Study of Single Cylinder Diesel Engine Using Pertadex Mixed Fuel with Rice Bran Biodiesel - Ady Ansyari Sirait (International Journal of Mechanical Computational and Manufacturing Research, 2021)
Increasing population, and limited resources of oil into so many things that encourage us to do the research and development of alternative fuels, one of which is the use of rice bran to produce biodiesel. Indonesia as the world's third largest grain, bran produced in large quantities. The content of free fatty acids (Free Fatty Acid (FFA)) is high, rice bran can be converted into Biodiesel. This study aims to analyze the performance of diesel engines using alternative fuel mixture Pertadex with 5%, 10%, 15%, 20%, 25%, 30% biodiesel rice bran. Stages of work done in this study, the manufacture of biodiesel by transesterification process, blending biodiesel with Pertadex, testing calorific value in a bomb calorimeter, and performance testing of diesel engines. From the analysis, it is concluded, greater the addition of a mixture% biodiesel Rated Power, volumetric efficiency, the actual Thermal Efficiency and Heat Loss tended to decline, while the rate of material flow baar (mf) and specific fuel consumption (SFC) Tend to increase.